2015
DOI: 10.5604/15093492.1186829
|View full text |Cite
|
Sign up to set email alerts
|

Knee Function and Subjective Stability Following Total Condylar Arthroplasty in Joints with Preoperative Varus or Valgus Deformity

Abstract: 1. In patients with proper implant alignment subjective instability is related to postoperative MCL deficiency, regardless preoperative deformity in coronal plane. 2. The post-op LCL laxity does not compromise subjective stability, nor influence subjective outcome, as demonstrated with KOOS scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In a study of the postoperative subjective stability of valgus and varus knees, the results showed that subjective instability was associated with postoperative MCL deficits. 18 In addition, differences in the severity of preoperative knee osteoarthritis and grade of valgus deformity were not associated with clinical outcome after TKA. 19 In our study, patients with valgus deformity had a total of five revisions, two of which were due to laxity of the medial collateral ligament, recurrence of valgus deformity of the knee, and instability.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In a study of the postoperative subjective stability of valgus and varus knees, the results showed that subjective instability was associated with postoperative MCL deficits. 18 In addition, differences in the severity of preoperative knee osteoarthritis and grade of valgus deformity were not associated with clinical outcome after TKA. 19 In our study, patients with valgus deformity had a total of five revisions, two of which were due to laxity of the medial collateral ligament, recurrence of valgus deformity of the knee, and instability.…”
Section: Discussionmentioning
confidence: 92%
“…The follow‐up of VTE after TKA has been rarely reported in previous studies, which only focused on overall postoperative complications. 17 , 18 , 19 Differently, in our study, the incidence of symptomatic VTE, the distribution of thrombus, and the radiographic features were described and recorded in detail for both the valgus and varus groups, and the differences in reasons for prosthesis revision were compared, which is more meaningful for clinical prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Due to excessive loads to the knee, it is known that MCL fibers, in particular, lose elasticity and contraction tension, which increases after postoperative knee correction in various patients who are morbidly obese, and relative laxity develops in the lateral collateral liga-ment. 30,35 Morbid obesity should be included among the risk factors for MCL injury, and we suggest that surgeons must be careful about medial loosening.…”
Section: Discussionmentioning
confidence: 98%